Canonical discriminant analysis of the fatty acid profile of muscle to authenticate beef from grass-fed and other beef production systems: Model development and validation. (April 2021) - Cama-Moncunill, R.; Moloney, A.P.; Röhrle, F.T.; Luciano, G.; Monahan, F.J.
Abstract: The potential of diet-induced differences in the fatty acid profile of muscle to discriminate beef from different feeding systems and its potential use as an authentication tool was investigated. Three canonical discriminant models were built and validated using the fatty acid profile of beef from animals fed solely on pasture or cereal-based concentrates for 11 months or on various pasture/grass silage/concentrate combinations, including concentrates enriched with plant oils. Results indicated that models could successfully discriminate between grass-, partially grass- and concentrate-fed beef (accuracy = 99%) and between grass-fed beef and beef from animals supplemented with plant oils (accuracy = 96%). The approach also showed potential for distinguishing between beef from exclusively pasture-fed cattle and beef from cattle fed on pasture preceded by a period on ensiled grass (accuracy = 89%). Models were also applied to beef samples from 9 different countries. Of 97 international samples, including samples stated to be grass-fed, only 5% were incorrectly classified as Irish-grass-fed beef. These results suggested that the models captured traits in the fatty acid profile that are characteristic of Irish grass-fed beef and that this feature could be used for distinguishing Irish grass-fed beef from beef from other regions. Graphical abstract: Image 1 Highlights: Muscle fatty acid profile was used to discriminate beef from various feeding systems. Canonical discriminant models were validated with an independent data set. Models were applied to an international set of beef samples. Beef from cattle fed grass, concentrate or combinations can be discriminated. Grass-fed beef can be distinguished from beef supplemented with vegetable oils.